2002
DOI: 10.1152/ajpendo.00072.2001
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced obesity and hepatic gene expression alterations in C57BL/6J and ICAM-1-deficient mice

Abstract: The effects of high-fat feeding on the development of obesity were evaluated in intercellular adhesion molecule-1 (ICAM-1) knockout and C57BL/6J (B6) male mice fed a high-fat diet for ≤50 days. Serum and tissues were collected at baseline and after 1, 11, and 50 days on the diet. After 11 days on the diet, ICAM-1-deficient, but not B6, mice developed fatty livers and showed a significant increase in inguinal fat pad weight. At day 50, ICAM-1-deficient mice weighed less, and their adiposity index and circulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
68
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 44 publications
(47 reference statements)
12
68
0
Order By: Relevance
“…Furthermore, previous studies have reported that steatotic livers produce increased levels of complement proteins de novo (46), which may also contribute to the apparent increase in C3d immunostaining. Nevertheless, CR2-Crry treatment resulted in a significant reduction in immunostaining for C3d in livers from both lean and steatotic mice after I/R and posttransplantation.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, previous studies have reported that steatotic livers produce increased levels of complement proteins de novo (46), which may also contribute to the apparent increase in C3d immunostaining. Nevertheless, CR2-Crry treatment resulted in a significant reduction in immunostaining for C3d in livers from both lean and steatotic mice after I/R and posttransplantation.…”
Section: Discussionmentioning
confidence: 94%
“…Although once thought to be expressed exclusively in adipocytes, adipsin mRNA is found in the gastrointestinal tract, spleen, and liver (16,29). Factor D is unique among complement components in that it does not require proteolytic processing for activation; and it exhibits exceptional specificity for its substrate C3bB (43).…”
Section: Discussionmentioning
confidence: 99%
“…This, of course, is not surprising, given the plethora of genes that are transcriptionally regulated by cellular uptake of cholesterol and fatty acids. For example, in a recent study of mouse liver gene expression, SREBP-1, apolipoprotein A-IV, and adipsin (factor D) were all upregulated by a Western diet (16). Most of these cholesterolgenic genes, however, are downregulated with high-fat feeding to varying degrees in both control and LDLR-deficient mice (and hence cluster in the lower portion of Fig.…”
Section: Liver Gene Expression In Atherosclerosis-prone Micementioning
confidence: 96%
“…6,7 C57BL/6J mice also develop fatty liver in response to an HF diet. [8][9][10] However, they are resistant to sucrose/fructose-induced fatty liver because they possess adenine Ϫ468 bp from the putative 5Ј end of the sterol regulatory element-binding protein (SREBP)-1c gene. 11 Mice with guanine at this site show increased liver SREBP-1c messenger RNA (mRNA) in response to a high-fructose diet, whereas mice with adenine do not.…”
mentioning
confidence: 99%